Working bodies : chronic illness in the Canadian workplace - Stone, Sharon Dale, 1955-; Crooks, Valorie A., 1976-; Owen, Michelle K. (Montréal ; Kingston : McGill-Queen's University Press, 2014)
While significant research has been produced in the field of disability studies, little attention has been paid to experiences of chronic illness. This book emphasizes the workplace as an important site for understanding such experiences, as employment status has an enormous impact on social and economic standing in Canadian society.
Part four : Epilogue. Narrative Preface: Andrea's Story / Andrea Black -- Epilogue / Sharon-Dale Stone, Valorie A. Crooks, and Michelle Owen.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Chronically ill -- Employment -- Canada; Chronically ill -- Canada -- Economic conditions; Chronically ill -- Canada -- Social conditions; Work environment -- Canada; Chronic diseases; Social history; People with disabilities; Chronic Disease; Social Conditions; Persons with Disabilities; Occupational Health; Workplace -- standards; Canada; Malades chroniques -- Travail -- Canada; Malades chroniques -- Canada -- Conditions économiques.; Malades chroniques -- Canada -- Conditions sociales; Maladies chroniques; Histoire sociale; Personnes handicapées.; social history; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Social history; People with disabilities; Chronic diseases; Work environment; Chronically ill -- Economic conditions; Chronically ill -- Employment; Chronically ill -- Social conditions; Canada; Electronic books